The Prognostic Impact of Age at Diagnosis Upon Breast Cancer of Different Immunohistochemical Subtypes: A Surveillance, Epidemiology, and End Results (SEER) Population-Based Analysis - Cai, Shibin; Zuo, Wenjia; Lu, Xunxi; Gou, Zongchao; Zhou, Yi; Liu, Pengpeng; Pan, Yin; Chen, Shuzheng (Frontiers in Oncology, 2020)
Background and Objectives: The influence of age at diagnosis of breast cancer upon the prognosis of patients with different immunohistochemical (IHC)-defined subtypes is still incompletely defined. Our study aimed at examining the association of age at diagnosis and risk of breast cancer-specific mortality (BCSM). Methods: 172,179 eligible breast cancer patients were obtained for our study cohort using the SEER database from 2000 to 2015. Patients were classified into four IHC-defined subtypes according to their ER, PgR and HER2 status. Kaplan-Meier plots were used to describe BCSM among patients in different age groups. A Cox proportional hazards model was used for multivariate analysis. A multivariable fractional polynomial model within the Cox proportional hazards model was used to evaluate the relationship between age at diagnosis and the risk of BCSM. Results: For the whole cohort, the median follow-up time was 43 months. Patients younger than 40 years and those older than 79 years presented with the worst BCSM (hazard ratio [HR] 1.13, 95% confidence interval [CI] 1.03-1.23 and HR 3.52, 95% CI 3.23-3.83, respectively, p < 0.01, with age 40-49 years as the reference). The log hazard ratios of hormone receptor (HoR) (+)/HER2(−) patients formed a quadratic relationship between age at diagnosis and BCSM, but not in the other 3 subtypes of breast cancer. In the HoR(+)/HER2(−) subtype, patients younger than 40 years had worse BCSM than those aged 40-49 years (HR 1.26, 95% CI 1.10-1.45, p < 0.01). Conclusions: Women diagnosed with HoR(+)/HER2(−) breast cancer at younger than 40 years or older than 79 years of age suffer higher rates of cancer-specific mortality. Young age at diagnosis may be particularly prognostic in HoR(+)/HER2(−) breast cancer.